ENTREPRENEURIAL MANAGEMENT OF SCHOOL PRINCIPALS IN IMPROVING EDUCATIONAL QUALITY AT JUNIOR HIGH SCHOOLS IN NORTH ACEH REGENCY - Antin Hasmiwati; Saiful Bahri; Najmuddin Najmuddin (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
This study aims to analyze the principal's application of entrepreneurial management in improving educational quality, particularly in terms of graduate standards, at SMP Negeri 1 Lapang, North Aceh Regency. Using a qualitative case study approach, this study examines entrepreneurial leadership practices that integrate educational management functions with a spirit of innovation and entrepreneurship. Data collection was conducted through interviews, observations, and documentation with the principal, teachers, school committee members, and business partners as the primary research subjects. Data analysis followed the Miles and Huberman model in an interactive and continuous manner. The results indicate that the principal applies entrepreneurial management in a visionary, adaptive, and collaborative manner through strategic planning, efficient organization, implementation of innovative project-based programs, and ongoing supervision involving various stakeholders. The impact is seen in improving student academic and non-academic learning outcomes, strengthening graduate competencies to be independent, creative, and innovative, and enhancing the school's reputation. Supporting factors for success include internal support from teachers and committee members, as well as external support from parents and business partners. While the main obstacles are limited facilities, budget, and bureaucratic regulations. Overall, consistent and participatory entrepreneurial management has proven effective in producing graduates who excel, possess character, and are highly competitive at both the local and regional levels.